Assessment of the relationship between C-Reactive Protein/Albumin ratio and 28-day mortality in critically very elderly patients (≥ 85 years) with acute ischemic stroke - Soylu, Veysel Garani; Karahan, Esma; Yılmaz, Ayşe; Taşkın, Öztürk; Demir, Ufuk (ASEAN Neurological Association, 2022)
Background & Objectives: The aim of this study is investigate the relationship of C-reactive protein, albumin, C-reactive protein/albumin ratio with prognosis and 28-day mortality in critically ill patients over 85 years of age with acute ıschaemic stroke. Methods: This study is a retrospective and observational study. A total of 189 patients aged 85 years and older who were followed up in the intensive care unit between 2017 and 2020 were included in the study. Demographic data of the patients included in the study, length of stay in the intensive care unit, comorbidities, laboratory data of hospitalization in the intensive care unit, C-reactive protein, albumin, C-reactive protein/albumin ratio, neutrophil/lymphocyte ratios, thrombocyte/lymphocyte ratios, APACHE II, SAPS II values of intensive care admissions were recorded. Results: In the statistical analysis performed for C-reactive protein, albumin, C-reactive protein/albumin ratio between survival and non-survival groups, a statistically significant difference was found between the groups (For C-reactive protein, p = 0.03; for albumin, p = 0.02; for C-reactive protein/albumin ratio, p= 0.03). The logistic regression model was applied to investigate the independent risk factors affecting the patients’ mortality at 28 days. Albumin, CRP , C-reactive protein/albumin ratio was found to be associated with 28-day mortality according to the logistic regression analysis. (For albumin; p= 0.04, for C-reactive protein; p= 0.04, for C-reactive protein/albumin ratio; p= 0.04). According to the ROC curve analysis result, Cut-off value was found to be 2.47 for C-reactive protein/albumin ratio. Conclusion: The CRP/albumin ratio is a valuable parameter that can be used to predict 28-day mortality in critically ill very elderly patients with acute ischemic stroke.
Keywords: 3. Good health